2017
DOI: 10.1007/s11356-017-0271-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes of chromium speciation and organic matter during low-temperature pyrolysis of tannery sludge

Abstract: The application or disposal of char derived from tannery sludge is directly influenced by the mobility and bioavailability of Cr during pyrolysis process. This study focused on the changes of Cr speciation and organic matter in tannery sludge during low-temperature pyrolysis (100-400 °C) to evaluate the toxicity of char in terms of the leaching possibility of Cr. The results showed that (1) lower char yield and more porous structure were observed after pyrolysis. (2) Higher pyrolysis temperature increased Cr c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
3
2
0
Order By: Relevance
“…In the temperature range of 400–1200 °C, the Cr mass content in the PDS char sample increases with the increase in the pyrolysis temperature. With the increase in the pyrolysis temperature, the fixing ratio of Cr showed a trend increasing gradually, and Zhou also obtained the same result. Because Cr is one kind of semivolatile heavy metal, the PDS sludge contains more chloride, and Cr may volatilize in the form of chromium chloride during pyrolysis.…”
Section: Resultssupporting
confidence: 53%
“…In the temperature range of 400–1200 °C, the Cr mass content in the PDS char sample increases with the increase in the pyrolysis temperature. With the increase in the pyrolysis temperature, the fixing ratio of Cr showed a trend increasing gradually, and Zhou also obtained the same result. Because Cr is one kind of semivolatile heavy metal, the PDS sludge contains more chloride, and Cr may volatilize in the form of chromium chloride during pyrolysis.…”
Section: Resultssupporting
confidence: 53%
“…The results of XRD analyses therefore indicated that the Cr(III) was the main form, and no Cr(VI)containing crystalline phases were found by XRD, which may be limited by the low Cr(VI) content compared to high amount of Cr(III). Similar results were found by Zhou et al (2018) who pyrolyzed tannery sludge during low temperature, and XRD results showed that no Cr(VI)-containing components were found by XRD although their tannery sludge had a high concentration of total Cr. In addition, no obvious mineral transform was found during the process of pyrolysis treatment at 300°C .…”
Section: Also Reportedsupporting
confidence: 85%
“…It was also reported by Zhou et al (2018) that the total concentration of Cr was high but lower in the leachate. The decrease of leachable Cr after co-pyrolysis treatments could be ascribed to the degradation of organic matter and the formation of undissolved compounds with calcium, copper and alkali.…”
Section: According To the Identification Standards For Hazardous Wastsupporting
confidence: 51%
“…It was deduced that Cr(III) may be oxidized to Cr(VI) during the calcination process forming soluble compounds that were responsible for the increased Cr leachability (Zhu et al, 2018). In contrast, the suppression of Cr leaching after pyrolysis may be due to the complexation with copper and calcium that could immobilize Cr (Zhou et al, 2018). Further, according to the 2003/33/EC, leaching of Clslightly exceeded (or around the borderline) the hazardous waste criteria in R-ESP (16873 ± 214 mg/kg) and C-ESP (17021 ± 203 mg/kg) samples after the pyrolysis experiment.…”
Section: Metal Leachingmentioning
confidence: 99%